Qawaid Ushuliah & Qawaid Fiqhiyah (Melacak Konstruksi Metodologi Istinbath al-Ahkam) - Adib Hamzawi (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2016)
Fiqh as the frame of life of Muslims to always walk in the rails of truth in the name of religion is a product ijtihad. As a product, there must be a manhaj or methodology and a set of rules used to construct it. For some Islamic law scholars, the rules governing the process of reasoning and the formulation of fiqh (istinbath al-ahkam) are often satisfied in the standard rules of usul fiqh and qawaid fiqh. Rarely there is a deeper scrutinize from which the rules contained in usul and qawaid fiqh are derived. Yet as a rule, there are certainly the basics that serve as guidelines for the preparation. Ushul fiqih and qawaid fiqih are built on the basis named ushuliyah rules and fiqhiyyah rules. Through the literature review, this paper examines the origins of the preparation of the rules that today have been recognized as the methodology of istimbath al-ahkam. So that Muslims understand how a legal product fiqih is processed from base to end. In addition, a qualified understanding of the construction of the birth of a methodology will lead to the birth of fiqh as a more academically recognized endowed product of idealistic academics.